A nomogram based on pretreatment clinical parameters for the prediction of inadequate biochemical response in primary biliary cholangitis. Issue 11 (11th September 2020) - Tian, Siyuan; Liu, Yansheng; Sun, Keshuai; Zhou, Xia; Ma, Shuoyi; Zhang, Miao; Zhou, Xinmin; Wang, Lu; Han, Ying
Abstract: Background: Ursodeoxycholic acid (UDCA) has been widely recommended as the first‐line drug for primary biliary cholangitis (PBC) in the current guidelines. However, its therapeutic effects are poor in nearly one‐third of patients. The early identification and intervention of these patients is crucial for delaying disease progression. Therefore, we explored risk factors for inadequate biochemical response and constructed a nomogram to predict the potential risk. Methods: We enrolled 356 patients and randomly divided them into training (70%) and validation groups (30%). We defined inadequate biochemical response as the study endpoint. Logistic analysis was used to identify the independent predictors of poor biochemical response. Based on these factors, a predictive nomogram was finally constructed. Then, discrimination and calibration were evaluated by internal validation. Additionally, the association between the model predictions and prognosis was further analyzed. Results: Female sex, and albumin and bilirubin concentrations were identified as risk factors, and a nomogram was built based on these factors. The areas under the ROC curves of the training and validation groups were 0.809 and 0.791, respectively. Moreover, calibration curves showed that predictions of the nomogram had good concordance with the actual outcomes. The correlation analysis demonstrated that PBC patients with a high probability of a suboptimal biochemical response were more likely to have adverse outcomes. Conclusion: We constructed a nomogram, which can accurately predict the risk of inadequate biochemical response to UDCA, facilitating the early screening of high‐risk patients with PBC who should be prioritized for additional therapy. Abstract : Flowchart of the study design.